Enhanced Thermoelectric Properties of Composites Prepared With Poly(3,4-Ethylenedioxythiophene) Poly(Styrenesulfonate) and Vertically Aligned Se Wire - Kim, In Yea; Chun, Dong Won; Kim, Sang-Il; Lim, Jae-Hong (FRONTIERS MEDIA SA, 2022)
Controlling the electronic transport behavior in thermoelectric composites is one of the most promising approaches to enhance their power factor because this enables decoupling of the correlation between the electrical conductivity and Seebeck coefficient. Herein, we show that the unexpected high power factor of the Se nanowire array embedded in poly(3,4-ethylenedioxythiophene)-poly(styrenesulfonate) (PEDOT:PSS) can be achieved by controlling the interfacial band structure engineering. The electrical conductivity and Seebeck coefficient simultaneously increased, confirming that the synthesis of organic/inorganic hybrid thermoelectric materials with improved performance was possible. Our exploration can be helpful for the rational design of high-performance thermoelectric composites through interface engineering.
Keywords: CHARGE-TRANSPORT; PERFORMANCE; FILMS; OPTIMIZATION; PEDOTPSS; FABRICATION; NANOWIRES